The Effectiveness Of The Cognitive Apprenticeship Model On The Reflective Thinking Skills Of Junior High School Students At Prof. Dr. H. Mohd. Hatta Education And Training Foundation (YPP) In Algebra Learning - Roni Darmawan; Tua Halomoan Harahap (EDUCATION JOURNAL OF INDONESIA, 2026)
This study aims to examine the effectiveness of the Cognitive Apprenticeship learning model on the mathematical reflective thinking skills of junior high school (MTs) students at YPP Prof. Dr. H. Mohd. Hatta in algebraic topics. This research is a quasi-experimental study utilizing a Non-equivalent Control Group Design. The research population comprised all seventh-grade students at MTs YPP Prof. Dr. H. Mohd. Hatta Stabat, with sample selection conducted through a cluster random sampling technique to determine the experimental class (Cognitive Apprenticeship learning) and the control class (conventional learning). The research instrument employed was a reflective thinking skills test consisting of essay questions on algebraic material that met the indicators of reacting, comparing, and contemplating. Data analysis was performed using the Independent Samples T-Test and the N-Gain Score test. The results indicated that the improvement in the reflective thinking skills of students taught with the Cognitive Apprenticeship model was significantly higher than that of students who received conventional learning. Consequently, the Cognitive Apprenticeship model is effectively implemented to optimize students' reflective thinking skills in algebra learning. Keyword : Cognitive Apprenticeship, Reflective Thinking, Algebra, Junior High School (MTs).